Special concert of the Vienna Philharmonic in Salzburg, Austria, conducted by Arturo Toscanini, August 24, 1937 (Austria; Salzburg, 2020)
Handbill advertising the special concert conducted by Arturo Toscanini in the Salzburg Festspielhaus, August 24, 1937, on the invitation of the National Broadcasting Co. of New York, to benefit the building fund and the pension fund of the Vienna Philharmonic. The program included Beethoven's Sixth Symphony.